Current Aspects of Non Hodgkin Lymphoma (NHL) In Bangladesh: A Mini Review - Rahman Bhuiyan, Md. Khaledur; Rahman, Dr. Mahmudur; Kumar Das, Swapan; Shahidul Islam, Dr. Syed Mahmood; Mahmud, Dr. Faiza; Mukit, Abdul; Malik, Javid Ahmad; Ahmed Mahedi, Md. Rezwan; Afrin, Sadia; Syrmos, Nikolaos (Clinical Medicine And Health Research Journal, 2023)
Approximately 90% of all lymphomas are classified as non-Hodgkin lymphoma (NHL), a subtype of lymphoma originating in other parts of the immune system outside the lymph nodes. Adult NHL may be classified as either B-cell lymphoma, T-cell lymphoma, or natural killer cell lymphoma, according to the World Health Organization's (WHO) categorization system. According to the statistics, about one and a half million new people are diagnosed with cancer in a year in Bangladesh, among which more than seven thousand people are affected by various blood cancers. Non-Hodgkin and Hodgkin lymphoma, leukaemia, and myeloma belong to blood cancers. Treatment also varies depending on the disease's type and stage or risk. The paper aims to express the current condition of NHL & the treatment approach for this disease by analysing the literature and data of Bangladesh.